RANCANG BANGUN MEKANISME TRANSMISI FESS (FLYWHEEL ENERGY STRORAGE SYSTEM) SEBAGAI ENERGI PADA MOBIL PENGGUNA KURSI RODA - Elsya Safira; Jecky Ardian; Abdi Fahruzi; Subkhan Subkhan (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Persons with disabilities are any person who experiences physical, intellectual, mental, and/or sensory limitations over a long period of time who in interacting with the environment may experience obstacles and difficulties to participate fully and effectively.. With it designed electric cars for wheelchair users that still carry aspects of safety, manufacturing and economy. The drive system needed in this car modification for people with disabilities uses an additional FESS (Flywheel Energy Storage System) system. FESS is an energy storage system on the flywheel that has a certain period and stores it as kinetic energy and releases energy significantly if the energy is needed (Adhe Anggry, 2016). The purpose of using FESS in this motion system is to save energy on MPKR. The method used in making this study was the design method of VDI 2222.